Retrospective and integrative analyses of molecular characteristics and their specific imaging parameters in pediatric grade 1 gliomas. Issue 8 (4th April 2022) - Coutant, Marie; Lhermitte, Benoit; Guérin, Eric; Chammas, Agathe; Reita, Damien; Sebastia, Consuelo; Douzal, Valérie; Gabor, Flaviu; Salmon, Alexandra; Chenard, Marie‐Pierre; Todeschi, Julien; Coca, Andres; et al.
Abstract: Background: Pediatric low‐grade gliomas (PLGG) are the most common brain tumors diagnosed during childhood and represent a heterogeneous group associating variable molecular abnormalities. To go further and develop specific statistical patterns between tumor molecular background, imaging features, and patient outcome, a retrospective study was performed in a group of non‐neurofibromatosis type 1 (non‐NF1) grade 1 PLGGs. Patients and methods: Seventy‐eight children, followed from 2004 to 2017, were retrospectively reported. In this population, we analyzed radiological and molecular parameters. Their therapeutic management comprised surgery or surgery plus chemotherapies. Results: Considering all 78 patients, 59 had only a surgical removal and 19 patients were treated with postoperative chemotherapy. Twelve progressions were reported in the partially resected and chemotherapeutic groups, whereas four deaths occurred only in the highly treated patients. As expected, in the global cohort, PLGG with BRAF p.V600E and/or CDKN2A loss exhibited poor outcomes and we evidenced significant associations between those molecular characteristics and their imaging presentation. In the chemo‐treated patients, when associating initial and 6‐month magnetic resonance imaging (MRI) parameters to the molecular features, the good risk situations were significantly linked to the presence of a large tumor cyst at diagnosis and the appearance during treatment of a higher cystic proportion that we called cystic conversion. Conclusion: So, additionally to the presence of BRAF p.V600E or CDKN2A deletion in grade 1 PLGGs, the absence on diagnostic MRI of cystic parts and/or cystic conversion at 6‐month chemotherapy were significantly linked to a worst prognosis and response to treatment. These imaging features should be considered as prognostic markers in future PLGG studies.